An experimental and modeling approach for ethanol production by Kluyveromyces marxianus in stirred tank bioreactor using vacuum extraction as a strategy to overcome product inhibition. (February 2019) - Tavares, Bruna; Felipe, Maria das Graças de Almeida; dos Santos, Júlio César; Pereira, Félix Monteiro; Gomes, Simone Damasceno; Sene, Luciane
Abstract: Vacuum ethanol removal effect on the fermentative performance of Kluyveromyces marxianus was assessed. Yeast was cultured in bench bioreactor at initial glucose concentration of 90 g L −1 in two sequential batches of 36 h, with a vacuum ethanol removal step and glucose feed before the second batch. Ethanol concentration after the first batch was 34.13 g L −1 (YP/S 0.38 g g −1 ; QP 0.94 g L −1 .h −1 ), and 40.90 g L −1 (YP/S 0.18 g g −1 ; QP 0.43 g L −1 .h −1 ) after the second batch. Ethanol production in a control assay without vacuum extraction only happened in the first batch (36.37 g L −1 ; YP/S 0.4 g g −1 ; QP 1.01 g.L −1 h −1 ). The phenomenological modeling showed product inhibition and the importance of product removal to process improvement, although the yeast had needed an adaptation period to recover its fermentative metabolism after the stress caused by vacuum. Highlights: Ethanol inhibition in K. marxianus was verified in two sequential batches intercalated by vacuum. Removal of ethanol by vacuum increased ethanol production. The cell-recovery time after the stress caused by vacuum must be considered.